Clinical Characteristic of Patients Underwent Bone Mineral Density Examination in Prof. Dr. R. Soeharso Orthopaedic Hospital in 2022-2023: A Cross-Sectional Study - Prijosedjati, R. Andhi; Utomo, Pamudji; Sabariyah, Leli; Fauzi, Ahmad ((JOINTS) Journal Orthopaedi and Traumatology Surabaya, 2024)
Background: In Indonesia, osteoporosis affects roughly 23% of men and women aged 50-70 and a staggering 53% of those over 70. Understanding the characteristics of patients undergoing bone mineral density (BMD) examinations is crucial for developing better strategies for prevention, diagnosis, and treatment. This study investigates the characteristics of patients who had BMD examinations at the Prof. Dr. R. Soeharso Orthopaedic Hospital. Methods: A cross-sectional study was conducted at Prof. Dr. R. Soeharso Orthopaedic Hospital from April 2022 to April 2023, using a total sampling approach and data extracted from digital medical records. The variables included age, gender, body mass index (BMI), BMD T-score from the lumbar spine, hip, and forearm, frequency and location of fragility fracture (FF), osteoporosis frequency, and fracture risk assessment (FRAX) score for major osteoporotic fracture (MOF) and hip fracture. Patients with incomplete data were excluded. Results: This study involved 168 patients, mainly women (83%) and men (17%). Most (81.5%) were aged 50-74, with osteoporosis affecting 29.2% and severe osteoporosis affecting 60.7%. The spine was the most common site of FF (88.2%). Osteoporosis severity correlated with higher BMI (p<0.05). FRAX scores for MOF and hip fractures were mostly in the low-risk category. Conclusions: A high prevalence of osteoporosis and severe osteoporosis among women, particularly those in the age of 50 to 74 years, and higher BMI was correlated with greater severity of osteoporosis. FF was found more common among women with the spine as the most frequently affected site.